Comparison of two delta-crystallin genes in the chicken. - Jones, R E (1980)
Restriction endonuclease mapping and electron microscopy established that there are at least two nonallelic delta-crystallin genes in the chicken. The structure of a complete delta-crystallin gene has been deduced by analysis of five cloned fragments from the chicken genome. Fifteen intervening sequences compose approximately 80% of this gene; the other gene contains at least 14 intervening sequences. The mRNA gene sequences appear to be similar; at least 60% divergence was found between the intervening sequences of the two delta-crystallin genes. Insertions or deletions or both appear to be major events responsible for these differences.